Association between choroid plexus volume and cognitive function in community-dwelling older adults without dementia: a population-based cross-sectional analysis - Yosuke Hidaka; Mamoru Hashimoto; Takashi Suehiro; Ryuji Fukuhara; Tomohisa Ishikawa; Naoko Tsunoda; Asuka Koyama; Kazuki Honda; Yusuke Miyagawa; Kazuhiro Yoshiura; Seiji Yuuki; Naoto Kajitani; et al. (Fluids and Barriers of the CNS)
Abstract Background An increase in choroid plexus (CP) volume may be associated with cognitive decline in older individuals without dementia. In this study, we aimed to clarify whether CP volume can serve as an imaging marker of cognitive decline, determine how strongly CP volume is associated with cognitive decline, and explore factors associated with CP volume in older adults. Methods We measured CP volume, brain parenchyma, and cerebrospinal fluid (CSF) spaces associated with disproportionately enlarged subarachnoid space hydrocephalus (DESH), an imaging feature of normal-pressure hydrocephalus, in community-dwelling older adults aged ≥ 65 years without dementia. Results In 1,370 participants, lower Mini-Mental State Examination (MMSE) scores were significantly associated with higher CP volume, even after adjusting for DESH-related CSF space and brain parenchymal volume. CP volume was more strongly associated with MMSE scores than DESH-related CSF space and brain parenchymal volume. History of smoking, white matter hyperintensity, enlarged perivascular spaces, age, body mass index, and diabetes mellitus were also associated with increased CP volume. Conclusions CP volume may be a highly sensitive imaging marker of cognitive decline in community-dwelling older adults without dementia, as it is linked to cognitive decline independently of brain parenchyma and CSF volumes. Our findings emphasize the importance of investigating CP volume increase to maintain cognitive function in older individuals. Accordingly, further longitudinal studies are required.